2016
DOI: 10.1177/0161734616680985
|View full text |Cite
|
Sign up to set email alerts
|

A Color-Doppler Shear-Wave-Imaging Phase-reconstruction Method Using Four Color Flow Images

Abstract: This study investigates shear wave phase map reconstruction using a limited number of color flow images (CFIs) acquired with a color Doppler ultrasound imaging instrument. We propose an efficient reconstruction method to considerably reduce the number of CFIs required for reconstruction and compare this method with Fourier analysis-based color Doppler shear wave imaging. The proposed method uses a two-step phase reconstruction process, including an initial phase map derived from four CFIs using an advanced ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…e 50% weight is currently known to be a better setting [11]. Sunaguchi et al [12] adopted an iterative method based on the advanced optical interference for CDFI reconstruction while ensuring the image quality and greatly reducing the phase artifacts in the initial phase map. Puchner et al [13] applied the IR algorithm to coronary vascular ultrasound images and found that IR could effectively improve the accuracy of semiautomatic plaque assessment.…”
Section: Introductionmentioning
confidence: 99%
“…e 50% weight is currently known to be a better setting [11]. Sunaguchi et al [12] adopted an iterative method based on the advanced optical interference for CDFI reconstruction while ensuring the image quality and greatly reducing the phase artifacts in the initial phase map. Puchner et al [13] applied the IR algorithm to coronary vascular ultrasound images and found that IR could effectively improve the accuracy of semiautomatic plaque assessment.…”
Section: Introductionmentioning
confidence: 99%